Pengaruh Harga terhadap Tingkat Penjualan pada Produk Kadoz di Kota Gunungsitoli - Harefa, Ronand Sona Sowa’a; Telaumbanua, Aferiaman; Laia, Otanius; Harefa, Idarni (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The purpose of this study was to determine the effect of price on sales levels of refill water products and how much price affects sales levels of refill water products in Kadoz, Gunungsitoli City branch. The research method used by the researcher is the Quantitative Method, because it is in line with the title and objectives raised regarding the relationship between variables with other variables. The type of research used by the researcher is the Quantitative Method, because it is in line with the title and objectives raised regarding the relationship between variables with other variables. The results of the study indicate that price has a positive and significant effect on sales levels of Kadoz products in Gunungsitoli City branch. This statement is based on the results of the t-test or hypothesis test by comparing the results of t count and t table that have been carried out by the researcher.